Uso do hipertexto: enunciação digital hibrida - na educação a distância - Faraco, Sabrina de Farias (2008)
With the intention of presenting the use of the hypertext in the relations dialógicas between pupils and teachers in the forums of the virtual environments of apprenticeship, like possible tool motivadora of the reading, we try to identify in two cutting out of forums of a virtual course of computer science, marks that were proving his use, as well as if this practice influences or not in the leituras during developing the discussions. Finding the hypertext an expressed digital hybrid (verbal resonant appearance), while a new enunciative technology, we present the principal characteristics that differentiate the hypertexts of the continuous linear texts, and discuss his implications so much in the development of new skills of reading and consequent increase of the interactivity, how much in the appearance of the conception of new authorships and in the construction of knowledge. Key words: Hypertext, Reading, Interactivity